Perancangan Aplikasi Pengenal Alat Musik Tradisional Gandara Menggunakan Multipoint Mouse SDK - Arena Bayu Chandra Permana; Kodrat Iman Satoto; Kurniawan Teguh Martono (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2014)
Young men nowadays have few interest with traditional art, including many kinds of Indonesia musical instruments. Compared with that traditional art, people are more familiar with multimedia application in computer devices. Based on those things, there is an idea to create a computer application to make famous Indonesia musical instruments by giving explanation and make a simulation. The application’s name is “Gandara”, a word from sanskrit language that means notes collection. “Gandara” uses MultiPoint Mouse SDK that makes the application to be able played by multiple users. The application is developed using Multimedia Development Life Cycle (MDLC) that consist of concept, design, material collecting, assembly, testing and distribution. “Gandara” users can learn both of gamelan and angklung by reading the explanation or playing the simulation. With this applicaton, users don’t need to face gamelan and angklung directly when they want to exercise. All of “Gandara” functions can work well when tested with black-box method and got positif results when tested by users.